THE SIGNIFICANCE OF THE RESEARCH OF FOREIGN EXPERIENCES IN THE DEVELOPMENT OF THE PROFESSIONAL MORALITY OF STUDENTS (Scientific journal of the Fergana State University, 2024)
This article presents important factors of research and conceptual aspects of foreign experiences on the development of students’ professional spirituality. Occupation is an activity that leads to self-awareness of a person, satisfaction from his work. It is shown that it is necessary to develop professional spirituality through education. The principles of professional ethics are explained.